2015
DOI: 10.1016/j.bbadis.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM6 promotes tumor angiogenesis and vasculogenic mimicry in gastric cancer via FAK signaling

Abstract: CEACAM6 is a member of glycosylphosphatidylinositol-linked immunoglobulin superfamily that is implicated in a variety of human cancers. In our previous study, we reported that CEACAM6 was overexpressed in gastric cancer tissues and promoted cancer metastasis. The purpose of this study is to determine the role of CEACAM6 in tumor angiogenesis and mimicry formation. We found that overexpressed CEACAM6 promoted tubule formation dependent on HUVEC cells and vasculogenic mimicry formation of gastric cancer cells; o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Tumor progression is not only associated with cancer cell metastasis, but also with tumor angiogenesis (3). There must be angiogenesis tubular formation in tumors with a diameter of ~2 mm (22).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor progression is not only associated with cancer cell metastasis, but also with tumor angiogenesis (3). There must be angiogenesis tubular formation in tumors with a diameter of ~2 mm (22).…”
Section: Discussionmentioning
confidence: 99%
“…In general, tumor progression is accompanied by rich angiogenesis to satisfy the metabolic requirements [11]. Tumor metastasis is a major contributor to cancer-related death and the process of capillary formation in tumor is a crucial aspect to enable metastasis, especially when tumors diameter approximates 2 mm [12]. The poor outcome of PaC is closely associate with the tendency to spread to surrounding tissues, approximately 50% of PaC patients present with distant metastatic disease [13], which is significantly correlated with the phenomenon of angiogenesis [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to inhibit the angiogenesis for PaC. However, traditional anti-vascular drug may promote tumor progression by inducing hypoxia which insteadly stimulates angiogenesis, so novel anti-vascular therapy should be applied [12]. To our knowledge, there are various molecular factors involved in vascular growth.…”
Section: Introductionmentioning
confidence: 99%
“…15,18 It was reported that the inhibition of tumor metastasis could remarkably enhance survival rates of tumor patients. 19 Octreotide (OCT) is a synthetic 8-peptide analog of somatostatin and mainly binds to somatostatin receptors that are overexpressed in a variety of tumors. 20,21 Somatostatin receptors have been recognized as tumor markers and are used for tumor diagnose and treatment.…”
Section: Introductionmentioning
confidence: 99%